The Role of Developing Country Firms in Infrastructure : New Data Confirm the Emergence of a New Class of Investors - Schur, Michael; Klaudy, Stephan von; Pushak, Nataliya; Sanghi, Apurva; Dellacha, Georgina (World Bank, Washington, DC, 2012)
Developing country investors have emerged as a major source of investment finance for infrastructure projects with private participation. This update of the article in 2006, shows that, indeed, during 1998-2006 these investors accounted for more of this finance in South Asia and East Asia and Pacific, and for more in transport across developing regions than did investors from developed countries. Even though the policy implications are not yet fully clear for policy makers, this development suggests a need to rethink the criteria used in selecting investors in schemes for private participation, which have been biased toward large international operators.